2022
DOI: 10.1021/acs.jpcc.2c01146
|View full text |Cite
|
Sign up to set email alerts
|

New Variant of Electrochemical Intercalation Isotherm: Analysis of Instability Region Dependence on Electrolyte Concentration

Abstract: Electroactive redox materials, encompassing redox polymers, metal−organic frameworks, and intercalation materials, play an important role in a wide range of emerging applications. However, many theoretical issues concerning quantitative thermodynamic description of such materials remain unclear so far. Existing variants of electrochemical intercalation isotherms (namely, the Langmuir−Frumkin isotherm, which often applies to redox polymers and electroactive solid materials, and the reformulated isotherm, accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Many redox polymers demonstrate narrow voltammetric peaks, which can be attributed to interspecies interaction. 90,91 The hybrid conducting redox polymers considered in this work are no exception: from Fig. 2 one can see that mid-widths of all TEMPO-related CV peaks are less than 130 mV, which strictly points to attractive short-range interactions between redoxcenters (details are given below in the chapter ''Approximation of experimental CV curves of conducting redox polymer films with the derived model'').…”
Section: Description Of a Thermodynamic Model For A Conducting Redox ...mentioning
confidence: 80%
See 2 more Smart Citations
“…Many redox polymers demonstrate narrow voltammetric peaks, which can be attributed to interspecies interaction. 90,91 The hybrid conducting redox polymers considered in this work are no exception: from Fig. 2 one can see that mid-widths of all TEMPO-related CV peaks are less than 130 mV, which strictly points to attractive short-range interactions between redoxcenters (details are given below in the chapter ''Approximation of experimental CV curves of conducting redox polymer films with the derived model'').…”
Section: Description Of a Thermodynamic Model For A Conducting Redox ...mentioning
confidence: 80%
“…This kind of approach has been widely used previously. 70,75,90,91 We should underline here that despite the fact that the capacity of electric double layers is considered to be negligibly small in comparison to the faradaic capacity of the bulk of the polymer material, the potential drop caused by EDL at both current collector/polymer film and polymer film/solution interfaces plays a substantial role in the developed model (see Fig. 1).…”
Section: Description Of a Thermodynamic Model For A Conducting Redox ...mentioning
confidence: 99%
See 1 more Smart Citation
“…4 are discussed in section S2 of the supplementary text. [36][37][38] Collectively, the potential drift profiles from Figs. 3b and 4 indicated that there were no significant contributions from electrode dissolution, faradaic processes, or other experimental anomalies.…”
Section: Resultsmentioning
confidence: 99%
“…Electrochemical ion intercalation plays an essential role in the study of batteries . Theoretical modeling of these processes has received considerable attention in particular concerning their voltammetric monitoring. The thermochemical aspects with separation of ion and electron transport contributions, the influence of solvation in aqueous and nonaqueous alectrolytes, and analysis of different electroinsertion regimes and phase transitions eventually accompanying it have been the focus of much of the recent research. , …”
Section: Introductionmentioning
confidence: 99%